Intergenerational transmission of parental smoking: when are offspring most vulnerable?. (17th July 2022) - Alves, J; Perelman, J; Ramos, E; Kunst, A E
Abstract: Background: Previous literature has showed that the likelihood of smoking is higher among offspring with smoking parents. The aim of this cohort study is to investigate during which smoking initiation stages and at what ages adolescents are more likely to be influenced by parental smoking. Methods: This study used the EPITeen Cohort, which recruited 13-year-old adolescents born in 1990, enrolled at schools in Porto, Portugal. Participants ( n  = 996) were followed across four waves at 13, 17, 21 and 24 years old. We computed the odds ratio (OR) and 95% confidence intervals for the prevalence of the different smoking states (never smoking, experimenter, less than daily smoker, daily smoker and former smoker), and incidence transitions between these states (to smoking experimenter; to less than daily smoker, to daily smoker; to former smoker) as function of age, parental smoking status and their interaction. Results: Compared with other participants, those with two smoking parents had an increased prevalence of experimentation at 13 years (OR for the interaction at 13 years compared with 24 years = 2.13 [1.50–3.01]) and daily smoking at all ages (OR for parental smoking =1.91 [1.52–2.40]). The latter increase is related to a significantly increased risk to transit from early smoking stages to daily smoking at all ages (OR for parental smoking = 1.83 [1.43–2.34]). Conclusions: Parental smoking influences offspring's daily smoking prevalence especially by increasing the risk to transit to daily smoking up to early adulthood. Prevention should focus on parents and parental influences especially among offspring who may transition to daily smokers.